Difference between revisions of "2005 Cyprus Seniors TST/Day 1/Problem 2"

(new)
 
(Solution)
 
Line 5: Line 5:
 
== Solution ==
 
== Solution ==
  
 +
Let <math>\alpha =y+z, \beta =x+z, \gamma =x+y</math>. Then the inequality becomes
 +
<math>2x(y+z)^2+2y(x+z)^2+2z(x+y)^2 \leq 3(x+y)(y+z)(z+x) </math>
  
 +
After expansion, it is equivalent to
  
 +
<math>x^2y+y^2x+x^2z+z^2x+y^2z+z^2y \geq 6xyz</math>
 +
 +
Which is true by <math>AM-GM</math> inequality
 
----
 
----
  

Latest revision as of 22:50, 12 October 2022

Problem

Given a triangle with sides $\alpha, \beta, \gamma$. Prove that: $\alpha^2 (\beta+\gamma-\alpha)+\beta^2 (\gamma+\alpha-\beta)+\gamma^2 (\alpha+\beta-\gamma)\leq 3 \alpha \beta \gamma$

Solution

Let $\alpha =y+z, \beta =x+z, \gamma =x+y$. Then the inequality becomes $2x(y+z)^2+2y(x+z)^2+2z(x+y)^2 \leq 3(x+y)(y+z)(z+x)$

After expansion, it is equivalent to

$x^2y+y^2x+x^2z+z^2x+y^2z+z^2y \geq 6xyz$

Which is true by $AM-GM$ inequality


See also